3.0=0.4m-2+0.2m

Simple and best practice solution for 3.0=0.4m-2+0.2m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.0=0.4m-2+0.2m equation:


Simplifying
3.0 = 0.4m + -2 + 0.2m

Reorder the terms:
3.0 = -2 + 0.4m + 0.2m

Combine like terms: 0.4m + 0.2m = 0.6m
3.0 = -2 + 0.6m

Solving
3.0 = -2 + 0.6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-0.6m' to each side of the equation.
3.0 + -0.6m = -2 + 0.6m + -0.6m

Combine like terms: 0.6m + -0.6m = 0.0
3.0 + -0.6m = -2 + 0.0
3.0 + -0.6m = -2

Add '-3.0' to each side of the equation.
3.0 + -3.0 + -0.6m = -2 + -3.0

Combine like terms: 3.0 + -3.0 = 0.0
0.0 + -0.6m = -2 + -3.0
-0.6m = -2 + -3.0

Combine like terms: -2 + -3.0 = -5
-0.6m = -5

Divide each side by '-0.6'.
m = 8.333333333

Simplifying
m = 8.333333333

See similar equations:

| 8w-3w-4w-1=32 | | (7y)^1/3 | | 10xt= | | 5x+10+x=-8 | | (5x+3)(2x-6)=0 | | px^2+qx+r=(x+1)(2x-7) | | 3x-2=x*x | | 3s-2s-1=29 | | 79=-7k | | 34/36 | | -29j+35j-(-39)=-33 | | (2x-2)(4x-7)=0 | | X/6-x/8=9 | | 3√7/9x2 | | 5y-8=8-4y-4 | | 12=-3(2-2r)-(2r+2) | | -2x(x^2+4x-5)=0 | | 35t-25t+10t-16t-3=49 | | 20=6x^2-7x | | x^y-^/x-4^y3^ | | 35k+7k-37k-k-3k+2=24 | | 4u+v-9u+18v= | | 3^sqrt7/9x^2 | | -26=-4(5-5n)-6(n-6) | | 43z-41z+5z=49 | | m^2+2m-7=8 | | 3u^2+u-14=0 | | 136.7784=3.14*r^2 | | 3(5)+y=14 | | 12-6x=-66 | | (5x+6)-(-2x^2-7x+6)=0 | | 5r-4r+(-4r)-18r-(-19r)=-8 |

Equations solver categories